Contact- and Water-Mediated Effects of Macroalgae on the Physiology and Microbiome of Three Indo-Pacific Coral Species - Fong, Jenny; Deignan, Lindsey K.; Bauman, Andrew G.; Steinberg, Peter D.; McDougald, Diane; Todd, Peter A. (Frontiers in Marine Science, 2020)
Competitive interactions between corals and macroalgae play an important role in determining benthic community structure on coral reefs. While it is known that macroalgae may negatively affect corals, the relative influence of contact- versus water-mediated macroalgal interactions on corals—such as via an influence on coral-associated microbiomes—is less well understood. Further, the impacts of macroalgae on corals that have persisted in a heavily urbanized reef system have not been explored previously. We examined the effects of the macroalgae Lobophora sp. and Hypnea pannosa on the physiology and microbiome of three Indo-Pacific coral species (Merulina ampliata, Montipora stellata, and Pocillopora acuta) collected from Singapore’s highly urbanized reefs, and compared how these effects varied between direct contact and water-mediated interactions. Direct contact by Lobophora sp. caused visible tissue bleaching and reduced Fv/Fm in all three coral species, while direct contact by H. pannosa only led to slight, but significant, suppression of coral Fv/Fm. No detrimental effects on coral physiology were observed when corals were in close proximity to the macroalgae or when in direct contact with algal mimics. However, both direct contact and water-mediated interactions with Lobophora sp. and H. pannosa altered the prokaryotic community structures in M. stellata. For M. ampliata and P. acuta, the changes in their microbiomes in response to algal treatments were more strongly influenced by the source reefs from which the coral colonies were collected. In particular, coral colonies collected from Kusu Island had proportionately more initial abundances of potentially pathogenic bacteria in their microbiomes than those collected from Pulau Satumu; nevertheless, coral fragments from Kusu Island had the same physiological responses to macroalgal interactions as corals from Pulau Satumu. Overall, our results reveal that, for the species tested, the coral microbiomes were sensitive to both direct contact and water-mediated interactions with macroalgae, while coral physiology was only compromised when in direct contact. Further, the presence of high levels of potentially pathogenic bacteria in some of the coral samples did not lead to the corals being more susceptible to impacts from macroalgae.